Evaluation of the Operational Modal Responses in Linear Switched Reluctance Actuators - Salvado, José A. (2020)
Submitted by CALADO (rc@ubi.pt) on 2020-01-06T15:45:54Z No. of bitstreams: 1 6.4.96_EEEIC_5_2018.pdf: 1904665 bytes, checksum: 622db9a4bcaebbe0501c6006fe385cd6 (MD5)